The spider sapphire mystery - Keene, Carolyn (New York : Grosset & Dunlap, 2000)
Nancy Drew's latest involvement in a mystery begins in her home town and concerns a synthetic sapphire with a spider embedded in it, and the strange disappearance of Ned Nickerson.
With: The invisible intruder, by Carolyn Keene. New York, Grosset & Dunlap, 1969.
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Detective and mystery stories, American